Influences of True Triaxial Loading-Unloading Stress Paths on Mechanical Properties and Wave Velocity of Coal Samples subject to Risk of Rock Burst - Wei Shen; Guang-Jian Liu; Lin-Ming Dou; Si-Yuan Gong; Hu He (Shock and Vibration)
To study fracture evolution and peak stress in burst risk coal samples (BRCSs) under true triaxial loading and unloading conditions, experimental and numerical research was applied to BRCSs under true triaxial stress paths entailing “x-direction displacement fixed, y-direction loading, z-direction unloading.” Both the experimental and the numerical results demonstrated that the peak stress borne by the BRCSs was not only affected by the initial stress but also had a negative exponential relationship with the ratio of the unloading rate and the loading rate (RURLR); therefore, peak stress equations of BRCSs under true triaxial loading and unloading conditions were established. The triaxial stress-time curves obtained by experiments and simulations exhibited an “elasticity-yield-destruction” phase, and the characteristics of the yield phase were determined by the RURLR. A typical BRCS was selected for velocity tomographic imaging to analyze the fracture evolution characteristics under true triaxial loading and unloading. The results showed that when the BRCS was subjected to a triaxial state of stress, the high- and low-velocity regions existed alternately due to the presence of the crack; during the elastic phase, the crack closed during loading in the previous phase was reopened upon unloading, so that the velocity of the sample decreased and a wide range of low-velocity regions could be formed; when entering the yield phase, the original crack continued to expand into a hole-through crack, leading to wider extreme values and ranges of these low- and high-velocity regions; at the breaking phase, multiple microcracks were generated around the hole-through cracks, decreasing the overall velocity, and showing point distributions characteristics of high- and low-velocity regions. Overall, many low-velocity regions with similar normal directions to the unloading direction were formed; these correlated well with macrofractures (postfailure).